2020
DOI: 10.3390/brainsci10040222
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, Adult Neuronal Stem Cells and Cells Migration in Pallium during Constitutive Neurogenesis and after Traumatic Injury of Telencephalon of Juvenile Masu Salmon, Oncorhynchus masou

Abstract: A study of the lateral pallium in zebrafish and the visual tectum of the medaka revealed a population of adult neuroepithelial (NE) cells supported from the early stage of development to various postembryonic stages of ontogenesis. These data emphasize the importance of non-radial glial stem cells in the neurogenesis of adult animals, in particular fish. However, the distribution, cell cycle features, and molecular markers of NE cells and glial progenitors in fish are still poorly understood at the postembryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 61 publications
(119 reference statements)
2
19
2
Order By: Relevance
“…The absence of Vim+ RG in the cerebellum of juvenile O. masou differs from the data of immunolabeling in adult A. leptorhynchus [ 27 ]. However, in general, it corresponds to the distribution of Vim+ NE cells in the telencephalon and in the mesencephalic tegmentum of juvenile chum salmon [ 14 , 15 ], and also agrees with the data of IHC labeling of vimentin for D. rerio [ 6 , 21 , 22 ]. Thus, the data obtained on juvenile masu salmon confirm the opinion that the population of Vim+ neuronal precursors is heterogeneous and probably has a different IHC signature of molecular markers, characterized by age-related and interspecies differences.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The absence of Vim+ RG in the cerebellum of juvenile O. masou differs from the data of immunolabeling in adult A. leptorhynchus [ 27 ]. However, in general, it corresponds to the distribution of Vim+ NE cells in the telencephalon and in the mesencephalic tegmentum of juvenile chum salmon [ 14 , 15 ], and also agrees with the data of IHC labeling of vimentin for D. rerio [ 6 , 21 , 22 ]. Thus, the data obtained on juvenile masu salmon confirm the opinion that the population of Vim+ neuronal precursors is heterogeneous and probably has a different IHC signature of molecular markers, characterized by age-related and interspecies differences.…”
Section: Discussionsupporting
confidence: 85%
“…Vimentin and nestin make up the cytoskeleton of NSCs and NPCs [ 50 , 51 ] and are considered as common markers of astrocytic glia in the vertebrate brain [ 29 , 50 ]. Previous studies on various parts of the brain of juvenile chum salmon, O. keta , showed that in the telencephalon [ 15 ] and the mesencephalic tegmentum [ 14 ], Vim+ cells correspond to NE precursors. The results of the study on chum salmon yearlings also showed that aNSCs/NPCs, phenotypically corresponding to RG cells, are generally not characteristic of the telencephalon and mesencephalic tegmentum of juvenile chum salmon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations